Reversibility of high pressure effects on the contractility of skeletal muscle. - Friedrich, Oliver; Kress, Kai; Ludwig, Horst; Fink, Rainer (Journal of Muscle Research and Cell Motility, 2001)
High pressure application has been extensively used to thermodynamically influence complex physiological processes such as membrane ion conductances and the mechanism of muscle contraction. However, little is known about the reversibility of high pressure effects on intact cells. Therefore, we studied the reversibility of 3 h pressure applications up to 25 MPa at +4 degrees C to intact murine skeletal muscle. Functional mechanical properties were tested in extensor digitorum muscle fibres skinned following a high pressure exposure. Calcium activated force and stiffness were nearly unchanged following pressure applications up to 20 MPa, whereas for higher pressures we found a marked reduction of peak force, a decline of activation kinetics, an increase of relaxation stiffness but still unchanged peak stiffness. The rigor kinetics showed a similar behaviour as the activation kinetics. pCa-force relations remained unchanged up to 20 MPa but were shifted towards smaller pCa values for higher pressures. In conclusion there is a rather sharp high pressure limit of 20 MPa above of which pressure application results in a substantial irreversible loss of contractile functionality in differentiated muscle which may at least partly be explained by changes in the Ca2+ regulatory process. This is supported by a degradation of the 37 kDa band, i.e. Troponin T, shown by SDS gel electrophoresis. However, the general stability of the other bands does not indicate a substantial increase of unspecific protease activity following a high pressure treatment up to 25 MPa.